- REVIEW ARTIKEL : Uji Iritasi Sediaan Topikal dari Tumbuhan Herbal: - - Sumarni, Ni Komang (Jurnal Jejaring Matematika dan Sains, 2022)
Irritation is an inflammatory phenomenon that occurs on the skin caused by the presence of foreign compounds on the skin. Factors that can cause irritation include contact time, penetration rate, area, and the level of toxicity of the materials used. Formulas and active substances used in a pharmaceutical preparation with a topical route can trigger side effects such as irritation of the skin. Thus, it is necessary to have a safety test that aims to meet product requirements before being marketed to the wider community. One of the safety tests that can be done is skin irritation test. Irritation testing can be carried out using four methods, namely draize, acute dermal, slug irritation test, and human patch test. The results of the study of 25 articles showed that only 16 preparations with herbal plant active substances had the best irritation index which was indicated by the irritation index (0.00) which means that the preparation did not irritate the skin. These plants are pomegranate peel, binahong leaves, jeruju leaves, red ginger, pinang seed husk, starfruit leaves, banana peel, clove flowers, seeds of papaya, shallot peel, ruruhi rind, sappan wood, pare fruits, eggplant peel, bay leaves, and longan leaves.